2011
DOI: 10.18359/rcin.270
|View full text |Cite
|
Sign up to set email alerts
|

Diseño de un sistema de recomendación en repositorios de objetos de aprendizaje basado en la percepción del usuario: Caso Rodas

Abstract: <span>Este trabajo presenta un sistema de recomendación (SR), de objetos de aprendizaje (OA), en repositorios. Es un sistema que se basa en el filtrado colaborativo que utiliza una adaptación del algoritmo k-vecinos y con fundamento en la percepción de usabilidad y utilidad que el usuario tiene acerca de los OA que descarga del repositorio. Tambien muestra la forma como el algoritmo k-vecinos se adaptó al concepto de percepción con la implementación de un sistema de votación de los OA por parte de los us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…In the Education field, the collaborative filtering method is observed to be used effectively in the recommendation system [15], [16] in line with the success of the content-based approach [17], [18] and recently the most widely used method is hybrid [19], [20] and context-aware/context-sensitive [21], [22]. However, some researchers also found that rating determination in the recommendation system in the field of Education stated as a cold start [24] In this regard, this study adopts a cognitive theory that describes learning as a business process which involves mental activities occurring in humans as a result of an active interaction with their environment to obtain a change in the form of knowledge, understanding, behavior, skills, values and attitude that are related and important.…”
Section: Introductionmentioning
confidence: 99%
“…In the Education field, the collaborative filtering method is observed to be used effectively in the recommendation system [15], [16] in line with the success of the content-based approach [17], [18] and recently the most widely used method is hybrid [19], [20] and context-aware/context-sensitive [21], [22]. However, some researchers also found that rating determination in the recommendation system in the field of Education stated as a cold start [24] In this regard, this study adopts a cognitive theory that describes learning as a business process which involves mental activities occurring in humans as a result of an active interaction with their environment to obtain a change in the form of knowledge, understanding, behavior, skills, values and attitude that are related and important.…”
Section: Introductionmentioning
confidence: 99%